A salty landscape of fear: responses of fish and zooplankton to freshwater salinization and predatory stress - Hintz, William D.; Relyea, Rick A. (Oecologia, 2017)
Predator–prey relationships are altered by anthropogenic contaminants. Road salt is a widespread contaminant among freshwater ecosystems, yet a relatively understudied subject in community ecology. Unknown is whether road salt salinization interacts with predatory stress to influence the growth, behavior, or reproduction of freshwater organisms. Using rainbow trout (Oncorhynchus mykiss) and zooplankton (Daphnia pulex), we exposed them to variable levels of road salt (NaCl) crossed with the presence or absence of alarm cues or kairomones. Alarm cue reduced trout activity and aggression and increased shoaling behavior. Road salt reduced trout growth in the high compared to moderate salt concentration, but neither concentration was different from the control. There was no interaction between alarm cues and salt for trout. Road salt and predatory stress had an additive effect on Daphnia abundance. Predatory stress decreased Daphnia abundance by 11 %. Compared to the control, salt decreased Daphnia abundance by 40 % in 860 mg Cl⁻/L and 79 % in 1300 mg Cl⁻/L, and by the final day abundance was reduced by 85 % in 1300 mg Cl⁻/L. Road salt and predatory stress had an interactive effect on Daphnia reproduction. Predatory stress in control water and moderate salt levels (230 mg Cl⁻/L) increased sexual reproduction of Daphnia, but these responses disappeared at high salt concentrations. Thus, road salt could limit reproductive adaptations to natural and anthropogenic stressors in Daphnia. Our results indicate road salt salinization could alter zooplankton population dynamics directly and by interacting with predatory stress, which might affect energy flow through freshwater food webs.